Brazil nut productive chain aspects in the state of Acre, Brazil - Bayma, Márcio Muniz Albano; Malavazi, Fernando Wagner; Sá, Claudenor Pinho de; Fonseca, Fernanda Lopes; Andrade, Edivaldo Pinheiro; Wadt, Lúcia Helena de Oliveira (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2014)
Few supply chains in the Brazilian state of Acre have shown as many changes as that of the Brazil nut. These changes have been driven a sequence of public policies as well as the recent development of a central cooperative of Brazil nut extractivists. Based on secondary data, this paper presents an analysis of key economic aspects features of the processing and commercialization of Brazil nuts, and in doing so seeks to improve understanding of the key structural changes that took place in this supply chain during the last ten years.